2015
DOI: 10.4103/0971-5916.160701
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors associated with domestic violence in urban slums, Mumbai, Maharashtra, India

Abstract: Background & objectives:Domestic violence is identified as a public heath problem. It is associated with adverse maternal health. This study examined the prevalence and determinants of domestic violence among women in urban slums of Mumbai, India.Methods:A community based cross-sectional household survey was carried out among eligible women for the study during September 2012 to January 2013. A total of 1137 currently married women aged 18-39 yr with unmet need for family planning and having at least one child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 29 publications
3
24
1
1
Order By: Relevance
“…This is contrary to women who reside in urban areas with wider access to higher education and opportunities; and therefore less likely to experience domestic violence. This is in consonance with several studies affirming that women who reside in rural areas are more likely to experience domestic violence compared to women residing in urban areas [10,28]. However, our study contradicts these findings above as there is no significant relationship between place of residence and acts of domestic violence.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is contrary to women who reside in urban areas with wider access to higher education and opportunities; and therefore less likely to experience domestic violence. This is in consonance with several studies affirming that women who reside in rural areas are more likely to experience domestic violence compared to women residing in urban areas [10,28]. However, our study contradicts these findings above as there is no significant relationship between place of residence and acts of domestic violence.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have reported that women are less educated, and pregnant with husbands who drink alcohol have higher risks to domestic violence [8][9][10][11][12][13][14][15][16]. Women who are less empowered, resides in rural areas and married to husbands who are from abusive homes, thus, ever experienced their father beating their mothers stands higher risks of domestic violence [10,15,[17][18][19][20][21][22][23][24]. Conversely, several literature evidenced that higher educational level for both women and men (husbands), women from wealthy families, empowered women and residing in urban areas were protective factors against domestic violence [11-13, 15, 19, 21, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Já no continente africano, encontrou-se que a taxa global de violência contra a mulher pelo parceiro foi de 70,2%, sendo que 55,3% sofreram algum tipo de abuso grave (16) . Os números menos alarmantes foram detectados em estudo realizado no continente asiático, no qual se constatou uma prevalência de 21,2% (26) . Estudos nacionais e internacionais fizeram uso das CTS2 para estimar a prevalência de violência por parceiro íntimo contra a mulher, e não foi relatado dificuldades para utilização da escala.…”
Section: Discussionunclassified
“…In addition, there was no study on neurological diseases. With regard to injury-related illnesses, which account for 5.9% of all studies, they were almost exclusively conducted on domestic (e.g., [71,72]) or partner-related violence (e.g., [73]). Mental health problems represent 5.6% of the total studies.…”
Section: Analysis By Health Categoriesmentioning
confidence: 99%